A study on the circular planform unmanned aerial vehicle - Mohamed Ali Suliman, Suliman Mohamed (Kulliyyah of Engineering, International Islamic University Malaysia, 2014)
In this work, aerodynamics investigation of the flow around the circular planform unmanned aerial vehicle (CP-UAV) was carried out numerically and validated with existencing published experimental data. The aircraft uses NACA 4412 airfoil. CD-Adapco STARCCM+ CFD software was used to simulate the flow. The simulations were carried out for three dimensional flows around CP-UAV to analysze the viscous flow behavior and aerodynamics coefficients such as boundary layer thickness, velocity vector contour, pressure distribution, streamlines, lift and drag coefficients. Three dimensional simulation was started with generating CATIA 3Ddrawing and exported to STAR-CCM+ for meshing. The numerical results of lift drag and moments coefficients were compared to experimental data. The qualitative comparison has shown acceptable good agreement. Finally, the study has shown that the CP-UAV is more stable and better aerodynamic characteristics than the conventional aircraft.